Challenges of Transit Oriented Development (TOD) in Iran. The Need for a Paradigm Shift - Mirmoghtadaee, Mahta (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Transit oriented development (TOD) has gained popularity as a means to address urbanizations problems such as traffic congestion, air pollution and affordable housing strategies. It simply refers to integration of urban development and public transportation facilities, together with some other characteristics such as “intensified land uses near TOD stations”, “landownership and car-ownership variety”, mixed use, “lower car dependency”, compact form, mass transit stations, open spaces, walkability, etc. The major contention of this paper is to discuss the general concept of TOD, its benefits and challenges in Iranian urban context. It is discussed here that TOD has several positive outcomes considering the existing urbanization trends in Iran. It may be used as a practical instrument to deal with rapidly urbanizing country in which motorization rate is increasing and air pollution is the serious cause of life loss. However there are several challenges which should be faced. The need for an Iranian version of TOD, which re-narrated the theory according to local situation, is the first challenge. A paradigm shift in the government, shifting the priority from housing schemes to mass transit systems is the second challenge needed to be taken into consideration. The third challenge is the overlapping and parallel institutions dealing with mass transit systems in urban and regional transportation planning and insufficient planning instruments. The integrated transportation and urban planning system is necessary here, and there is an urgent need to develop a national TOD guideline with the potential to develop local versions for each city.